Journeys to Africa in Gallica's digital library: modeling of intercultural interfaces in research-creation - (:unkn) unknown (My University, 2019)
This article presents the experimentation and the work from a research program of the French national Library and an IDEFI-CréaTic laboratory workshop dedicated to the editorialization of digital collections. It involves designing innovative mediation interfaces to the digital library Gallica's corpus "Journeys to Africa", with a postcolonial perspective. We adopt a theoretical-practical approach to question the notion of interculturality through the design of interfaces with an intercultural aim, whose ambition is to connect knowledge produced over the centuries by Europeans, Arabs and Africans.
Keywords: African Research